The Dynamic Electrocardiogram Pattern of T Wave Inversion Following ST Segment Elevation in Acute Coronary Syndrome with Non Significant Coronary Artery Disease - Anggoro Budi Hartopo; Hariadi Hariawan; Nahar Taufiq (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
ST segment elevation acute myocardial infarction (STEMI) is sometime indicated by typical electrocardiogram pattern, and rarely by atypical pattern. The definite diagnosis of STEMI is important to be determined rapidly and timely and becoming the key management success. The 12 lead electrocardiogram is the main diagnostic tool which should be completed and interpreted as soon as possible on patient admission. In the case, a female patient with anginal chest pain and initial ST segment elevation in electrocardiogram with non significant coronary artery disease. The subsequent electrocardiogram shows T wave inversion evolution pattern.Keywords: STEMI; T wave inversion; variant angina; evolution